Vander's human physiology the mechanisms of body function - Widmaier, Eric P.; Raff, Hershel; Strang, Kevin T. (McGraw-Hill education, 2019)
Vander's Human Physiology: The Mechanisms of Body Function. Moving beyond the listing of mere facts, it stresses the causal chains of events that constitute the mechanisms of body function. The fundamental purpose of this textbook is to present the principles and facts of human physiology in a format that is suitable for undergraduates, regardless of academic background or field of study. Vander's Human Physiology, fifteenth edition, carries on the tradition of clarity and accuracy, while refining and updating the content to meet the needs of today's instructors and students. The new edition offers an integrated package of textual and digital material to help deliver basic and clinical content, real-life applications, and educational technologies to students of physiology.